Синтез та особливості будови 2-аміно-3-бензтіазоліл-4(5Н)-кетопіролатів цинку - Нікітін, С.О.; Лампека, Р.Д.; Шишкіна, С.В.; Шишкін, О.В.; Воловненко, Т.А.; Воловенко, Ю.М. (Видавничий дім "Академперіодика" НАН України, 2008)
Three new ligands have been synthesized and characterized by means of IR and ¹H-NMR spectroscopies. The crystal structure of ligand HL³ is determined. The zinc complexes on the basis of 2-amino-3-benztiazolyl-4(5H)-ketopyrroles (HL¹−HL³) are prepared and studied by the spectroscopic method. The bidentate coordination of ligands through nitrogens of the heterocyclic substitute and the aminogroup is proposed with regard for the IR and ¹H-NMR spectra of complexes.